Dermatologic conditions of adult refugees following resettlement in the United States, 2015 to 2018 - Ann Hui Ching; Tricia Tay; Bryan Brown; Amir M. Mohareb; Aisha Sethi; Aniyizhai Annamalai (Journal of Migration and Health, 2023)
Background: There is a paucity of literature regarding dermatologic conditions in migrant and refugee populations. Methods: We conducted a cross-sectional study of all adult refugees resettling in a region of Connecticut, U.S. from 7 January 2015 to 20 November 2018. We conducted a manual chart review to determine dermatologic conditions diagnosed during and within one year of resettlement. We used multivariable logistic regression to determine demographic and clinical factors associated with having any dermatologic condition. Results: We included 545 refugees primarily from Afghanistan (40.6%), Syria (24.6%) and Iraq (10.5%), with a median (interquartile range) age of 33 (28–40) years. Of the 545 participants, 213 (39.1%) had dermatologic conditions. Fifty-four participants (25%) had more than one dermatologic condition and 114 (53.5%) were diagnosed within the first month of resettlement. The most common categories of conditions were cutaneous infections (24.9%), inflammatory conditions (11.1%), and scar or burn (10.7%). Tobacco use was associated with having a cutaneous infection (OR 2.37, 95%CI:1.09–4.95), and younger age was associated with having a scar or burn (for each year increase in age, OR 0.95, 95%CI:0.91–0.99). Conclusion: Dermatologic conditions are common among adult refugees. The majority of conditions were diagnosed in the first month following resettlement suggesting that a high number of dermatologic conditions arise or go undetected and untreated during the migration process.